2013
DOI: 10.7150/thno.3791
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Driven Design of Radionuclide Tracers for Non-Invasive Imaging of uPAR and Targeted Radiotherapy. The Tale of a Synthetic Peptide Antagonist

Abstract: Research performed during the last two decades has provided a wealth of information to highlight the role of the urokinase-type plasminogen activator receptor (uPAR) in the progression and dissemination of invasive and metastatic cancer. In parallel, our perception of the structure-function relationships in uPAR has been refined to such a level that a rational design of uPAR function as well as compounds specifically targeting defined functions of uPAR are now realistic options. This knowledge opens new avenue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 64 publications
0
29
0
Order By: Relevance
“…S1). The founding member of this subgroup is uPAR, which is by far the best characterized member, both structurally and functionally (Kriegbaum, Persson, et al 2011;Ploug 2013). Recent studies have clearly demonstrated that the interdomain flexibility of its three LU-domains enables an allosteric regulation of uPAR, where receptor occupancy with its high-affinity serine protease ligand, uPA, affects the subsequent interaction of uPAR with the extracellular matrix component vitronectin Gårdsvoll, Kjaergaard, et al 2011;Mertens et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…S1). The founding member of this subgroup is uPAR, which is by far the best characterized member, both structurally and functionally (Kriegbaum, Persson, et al 2011;Ploug 2013). Recent studies have clearly demonstrated that the interdomain flexibility of its three LU-domains enables an allosteric regulation of uPAR, where receptor occupancy with its high-affinity serine protease ligand, uPA, affects the subsequent interaction of uPAR with the extracellular matrix component vitronectin Gårdsvoll, Kjaergaard, et al 2011;Mertens et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Both uPAR wt ·8B12 (4QTI) and uPAR H47C-N259C (3U74) represent structures with an unoccupied but correctly assembled hydrophobic uPA binding cavity. A relatively large deviation (rmsd, 11.7 Å) is only observed for the structure of uPAR in complex with a non-natural synthetic 9-mer peptide antagonist (1YHW), which is currently being used as targeting principle for non-invasive positron emission tomography imaging of uPAR expression in vivo [35,36]. From these structural considerations, it is therefore clear that the mere binding of 8B12 Fab fragments drives the inherently flexible and unoccupied multidomain uPAR [29] into a closed conformational state resembling that adopted in the natural bimolecular and trimolecular uPAR·ATF and uPAR·-ATF·SMB complexes.…”
Section: Global Structure Of the Upar·8b12 Complexmentioning
confidence: 98%
“…These two proteins are predicted structural homologs belonging to the Ly6/uPAR/α-neurotoxin (LU) protein domain family. Along with the urokinase-type plasminogen activator receptor, uPAR (Ploug 2013), TEX101 (Fujihara et al 2013) and CD177 (Hu et al 2014), they constitute the few multidomain members of this family, all of which are encoded by a small gene cluster located on human chromosome region 19q13 (Jacobsen and Ploug 2008). Immunohistochemical surveys of resected organs from mice demonstrate that C4.4A is predominantly expressed in stratum spinosum of the squamous epithelium (Kriegbaum et al 2011), whereas Haldisin expression primarily is confined to stratum granulosum (Gårdsvoll et al 2013).…”
Section: Introductionmentioning
confidence: 99%